Peningkatan Daya Saing Usaha Mikro Kecil Dan Menengah Melalui Jaringan Usaha - Dandan Irawan (Coopetition : Jurnal Ilmiah Manajemen, 2020)
Increasing competitiveness in MSMEs must be gradual, meaning increasing competitiveness begins with efforts to win the competition. To find out the various conditions of MSME competitiveness, it is necessary to have a form of continuous development, in order to improve the standard of living for MSMEs in the country. The orientation and focus of empowering MSMEs need to be improved, such empowerment includes providing easy access to company functions and providing supporting facilitation, so that MSMEs are truly able to apply the general rules that apply in the economy in a consistent and consistent and effective manner. One effort that can be done is to conduct a strong business network. Business Network is one of the important factors in the UMKM business to increase economies of scale, manage business efficiently and expand market share. MSMEs that have a strong business network will be the capital to be able to carry out their operations effectively and efficiently, so that the business network can also become a capital for company competitiveness.